Potential role of PKC inhibitors in the treatment of hematological malignancies - Mischiati, C.; Melloni, E.; Corallini, F.; Milani, D.; Bergamini, C.; Vaccarezza, Mauro (2008)
The serine/threonine protein kinase C (PKC) family, the main target of tumor-promoting phorbol esters, is functionally associated to cell cycle regulation, cell survival, malignant transformation, and tumor angiogenesis. Although PKC isozymes represent an attractive target for novel anticancer therapies, our knowledge of PkC in tumorigenesis is still only partial and each PKC isoform may contribute to tumorigenesis in a distinct way. Specifically, PKC isoforms have wide and different roles, which vary depending on expression levels and tissue distribution, cell type, intracellular localization, protein-protein and lipid-protein interactions. Although PKC activation has been linked to tumor cell growth, motility, invasion and metastasis, other reports have shown that some PKC isoforms can also have opposite effects. Therefore, it will be necessary to analyze the relative contribution of each PKC isozymes in the development and progression of different tumors in order to identify therapeutic opportunities, using either PKC inhibitors or PKC activators as molecular tools of investigation. This minireview is focussed on the role of PKC signaling and on the perspective of PKC inhibition in hematological malignancies. © 2008 Bentham Science Publishers Ltd.